Enseñanza/aprendizaje en línea, perspectiva estudiantil en la ESPAM-MFL, durante la pandemia de la COVID-19, Manabí, periodo 2020/2021 - Balarezo Vélez, Sandra Paola (2022)
ESPAM-MFL student perception of the online modality experience during COVID19, period 2020-2021 was established. A total of 1754 students were surveyed to examine, students' perspectives on the online modality experience, how the E-learning platforms influenced their understanding and assimilation in knowledge transfer and in what context they would like the university to continue using these platforms. Multiple regression techniques were applied. Digital differences of 70 % and 30 % with network access or connection problems showed the gulf between rural and urban areas. Forum activity is a reliable predictor of academic performance and critical thinking in higher education institutions. A total of 1554 students surveyed do not express their opinion on the respect of class start time, breaks or termination of classes, when there are theoretical hours, hours in other scenarios, hours of the autonomous component that must be fulfilled within the Analytical Program of the Subject and syllabi. The ability to learn and assimilate information in the context of exclusively online learning was positive. Students frequently used the platform for assignments in word/pdf format (which could only be viewed by the teacher) in 83 %. The concentration on one variable would reflect the challenge of meeting certain preconditions for e-learning, such as access to multiple ICT tools and network infrastructure.